Wnt Site Signaling Inhibitor Secreted Frizzled‐Related Protein 3 Protects Mitral Valve Endothelium From Myocardial Infarction–Induced Endothelial‐to‐Mesenchymal Transition - Zahra Alvandi; Yasufumi Nagata; Livia Silva Araúujo Passos; Ali Hashemi Gheinani; J. Luis Guerrero; Jill Wylie‐Sears; Dayana Carolina Romero; Brittan A. Morris; Suzanne M. Sullivan; Koushiar M. Yaghoubian; Amirhossein Alvandi; Rosalyn M. Adam; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background The onset and mechanisms of endothelial‐to‐mesenchymal transition (EndMT) in mitral valve (MV) leaflets following myocardial infarction (MI) are unknown, yet these events are closely linked to stiffening of leaflets and development of ischemic mitral regurgitation. We investigated whether circulating molecules present in plasma within days after MI incite EndMT in MV leaflets. Methods and Results We examined the onset of EndMT in MV leaflets from 9 sheep with inferior MI, 8 with sham surgery, and 6 naïve controls. Ovine MVs 8 to 10 days after inferior MI displayed EndMT, shown by increased vascular endothelial cadherin/α‐smooth muscle actin–positive cells. The effect of plasma on EndMT in MV endothelial cells (VECs) was assessed by quantitative polymerase chain reaction, migration assays, and immunofluorescence. In vitro, post‐MI plasma induced EndMT marker expression and enhanced migration of mitral VECs; sham plasma did not. Analysis of sham versus post‐MI plasma revealed a significant drop in the Wnt signaling antagonist sFRP3 (secreted frizzled‐related protein 3) in post‐MI plasma. Addition of recombinant sFRP3 to post‐MI plasma reversed its EndMT‐inducing effect on mitral VECs. RNA‐sequencing analysis of mitral VECs exposed to post‐MI plasma showed upregulated FOXM1 (forkhead box M1). Blocking FOXM1 reduced EndMT transcripts in mitral VECs treated with post‐MI plasma. Finally, FOXM1 induced by post‐MI plasma was downregulated by sFRP3. Conclusions Reduced sFRP3 in post‐MI plasma facilitates EndMT in mitral VECs by increasing the transcription factor FOXM1. Restoring sFRP3 levels or inhibiting FOXM1 soon after MI may provide a novel strategy to modulate EndMT in the MV to prevent ischemic mitral regurgitation and heart failure.